Survivors' experiences of sexual assault by intimate partners: a qualitative study of survivors and their informal supports - Ullman, Sarah E. (Journal of family violence, 2024)
Sexual assault occurring in the context of intimate partner violence (IPV) relationships has received much less attention in the literature on sexual assault. Studies of both survivors and their informal support network members are also lacking in both sexual assault and IPV literatures. Purpose: The current study’s purpose was to examine sexual assault survivors’ experiences where intimate partner violence was mentioned as part of their narratives.MethodSurvivors and their informal support providers (SP; e.g., family, friends, romantic partners) were interviewed separately about disclosure, social reactions, and help-seeking following assault. Twenty-nine survivors and 12 informal support persons they told about their assaults mentioned survivor experiences of IPV-related sexual assault (IPVS). Results: Several themes emerged from the analysis of codes related to the traumatic event of IPV: 1) Severe physical violence in an intimate partner relationship; 2) use of violence for sexual gratification; 3) connecting trauma to other behavior, 4) unwanted duty and redefining abuse, and 5) state responses to IPVS. Conclusions: Implications are drawn for future research and practice on IPVS with survivors and their informal support networks.